Androgen Regulates Brain-Derived Neurotrophic Factor in Spinal Motoneurons and Their Target Musculature - Verhovshek, Tom (The Endocrine Society, 2010)
Trophic factors maintain motoneuron morphology and function in adulthood. Brain-derived neurotrophic factor (BDNF) interacts with testosterone to maintain dendritic morphology of spinal motoneurons. In addition, testosterone regulates BDNF’s receptor (trkB) in motoneurons innervating the quadriceps muscles as well as in motoneurons of the highly androgen-sensitive spinal nucleus of the bulbocavernosus (SNB). Given these interactive effects, we examined whether androgen might also regulate BDNF in quadriceps and SNB motoneurons and their corresponding target musculature. In both motoneuron populations, castration of males reduced BDNF immunolabeling, and this effect was prevented with testosterone replacement. ELISA for BDNF in the target musculature of quadriceps (vastus lateralis, VL) and SNB (bulbocavernosus, BC) motoneurons revealed that BDNF in the VL and BC muscles was also regulated by androgen. However, although castration significantly decreased BDNF concentration in the VL muscle, BDNF concentration in the BC muscle was significantly increased in castrates. Treatment of castrated males with testosterone maintained BDNF levels at those of intact males in both sets of muscles. Together, these results demonstrate that androgens regulate BDNF in both a sexually dimorphic, highly androgen-sensitive neuromuscular system as well as a more typical somatic neuromuscular system. Furthermore, in addition to the regulation of trkB, these studies provide another possible mechanism for the interactive effects of testosterone and BDNF on motoneuron morphology. More importantly, by examining both the motoneurons and the muscles they innervate, these results demonstrate that within a neural system, BDNF levels in different components are differentially affected by androgen manipulation.